SNPS em genes candidatos para potencial atlético como possíveis marcadores para desempenho em corrida em equinos da raça quarto de milha - Pereira, Guilherme Luis [UNESP] (2014)
In the Quarter Horse, different selection objectives led to the formation of lines with different skills, including racing and cutting. Less effective, but with great economic representation, the racing line present great sprinting speed over short distances on straight tracks. The cutting line is intended to evidence of functional character, exploring skills such as agility and obedience. The main objectives of this study were to estimate the allele and genotype frequencies of the g.38973231A>G (PDK4) and g.22684390C>T (COX4I2) SNPs in Quarter Horses (racing and cutting lines), as well as, in the racing line, to assess the occurrence of associations of these polymorphisms with performance trait (SI - speed Index); (2) verify the occurrence of differences in allele frequencies of g.66493737C>T (MSTN) and g.22999655C> (DMRT3) SNPs in racing line of contrasting to IV, and (3) to estimate genetic and environmental parameters for body measurements and IV of the racing line. The results showed the MSTN gene with the C allele near fixed with just an animal heterozygote (CT). In the analysis of 296 racing animals and 68 cutting animals, the differences in allele and genotype frequencies were statistically significant for PDK4 and COX4I2 genes between the two lines. The same was not observed when these frequencies were compared between extreme phenotypes race. There was also no significant effects on test of association between the alleles of the two polymorphisms and IV. The g.22999655C>A (DMRT3) SNP was genotyped in 60 animals. Heritability from 0.21 to 0.69 for morphometric traits and 0.17 for IV were observed. There was moderate negative correlation between body and rump length and performance (-0.44 and -0.30, respectively) and low positive correlation between height at withers and performance (0.25) that alleles. These results suggest of PDK4 and COX4I2 genes associated with better performance in race of PSI, perhaps are related ...